Records of some rare deep-sea fishes caught in the Lion, Susan, and Unicorn seamounts, off the archipelago of Madeira (east-central Atlantic) - J. Delgado; D. Carvalho; M. Freitas; M. Biscoito; E.P. Gouveia (Acta Ichthyologica et Piscatoria, 2017)
Fish communities off the seamounts inside the Madeira exclusive economic zone are scarcely known, hence the need to improve this knowledge. A bottom trawl fishing survey targeting orange roughy, Hoplostethus atlanticus Collett, 1889, was carried out on the Lion, Susan, and Unicorn seamounts in the autumn of 2001. The aim of this paper is to give an account of the catches of that survey, during which 9 tows were conducted and 21 deep-sea fish species caught, including species rarely caught. The following fish species were collected: Chlamydoselachus anguineus Garman, 1884; Scymnodon ringens Barbosa du Bocage et de Brito Capello, 1864; Dalatias licha (Bonnaterre, 1788); Centrophorus squamosus (Bonnaterre, 1788); Deania profundorum (Smith et Radcliffe, 1912); Deania hystricosa (Garman, 1906); Serrivomer beanii Gill et Ryder, 1883; Rouleina maderensis Maul, 1948; Argyropelecus gigas Norman, 1930; Chauliodus sloani Bloch et Schneider, 1801; Macroparalepis nigra (Maul, 1965); Neoscopelus microchir Matsubara, 1943; Gadomus arcuatus (Goode et Bean, 1886); Mora moro (Risso, 1810); Melanonus zugmayeri Norman, 1930; Chaunax suttkusi Caruso, 1989; Diretmoides pauciradiatus (Woods, 1973); Hoplostethus mediterraneus Cuvier, 1829; Beryx splendens Lowe, 1834; Epigonus telescopus (Risso, 1810); Aphanopus carbo Lowe, 1839. The presence of Diretmoides pauciradiatus was confirmed in the area and Gadomus arcuatus was recorded for the first time from Madeira. Aspects of the life history traits of some of the species caught are presented. This includes a first approach to the estimation of the length–weight relations of 11 deep-water, data-deficient species for which prior information, estimated from data collected, did not exist in FishBase and some new insights about the biology of Hoplostethus mediterraneus.